2010
DOI: 10.1051/0004-6361/200913281
|View full text |Cite
|
Sign up to set email alerts
|

Statistics of the sodium layer parameters at low geographic latitude and its impact on adaptive-optics sodium laser guide star characteristics

Abstract: Aims. To aid the design of laser guide star (LGS) assisted adaptive optics (AO) systems, we present an analysis of the statistics of the mesospheric sodium layer based on long-term observations (35 years). Methods. We analyze measurements of the Na-layer characteristics covering a long period , acquired at latitude 23 • south, in São José dos Compos, São Paulo, Brazil. We note that Paranal (Chile) is located at latitude 24 • south, approximately the same latitude as São Paulo.Results. This study allowed us to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
1

Year Published

2010
2010
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 24 publications
4
27
1
Order By: Relevance
“…11). The correction also leads to the rise of the Na lines to altitude values of ≈80 km, a value in agreement with the literature (Plane 2003;Moussaoui et al 2010). Nevertheless, the width of the terrestrial Na I peaks are observed to be ≈0.4 Å.…”
Section: Results From Eq (1) (Method1)supporting
confidence: 90%
See 1 more Smart Citation
“…11). The correction also leads to the rise of the Na lines to altitude values of ≈80 km, a value in agreement with the literature (Plane 2003;Moussaoui et al 2010). Nevertheless, the width of the terrestrial Na I peaks are observed to be ≈0.4 Å.…”
Section: Results From Eq (1) (Method1)supporting
confidence: 90%
“…It is indeed known that meteor showers can temporarily increase the amount of sodium in the atmosphere by a factor up of 10 (Plane 2003;Moussaoui et al 2010). This corroborates the detection of the sodium layer by Vidal-Madjar et al (2010) in August 2008.…”
Section: Results From Eq (1) (Method1)mentioning
confidence: 99%
“…NaI is known to be present in the Earth atmosphere within a layer at about 92 km, presenting an average thickness of about 11 km (Moussaoui et al 2010). If it was completely opaque in the two NaI lines, we should have found the same level in both lines at lower altitudes than the 92 km, depending on the ratio between the atmospheric line width (∼0.03 Å) and the instrument spectral resolution (∼0.09 Å).…”
Section: Sodium Detectionmentioning
confidence: 86%
“…For an ELT, with elongation varying more significantly across the WFS, the total performance gain may be smaller, though still significant. We also note that the LGS elongation was varying during the night and from night to night, following the sodium layer thickness variations (Moussaoui et al 2010). …”
Section: On-sky Results Summarymentioning
confidence: 78%